Civilizational collapse and the philosophy of post-apocalyptical survival - Besley, Tina; McCarthy, Cameron; Rizvi, Fazal; Peters, Michael Adrian; Meier, Thomas (Peter Lang Inc., International Academic Publishers, 2025)
The collapse of civilization, the end of the world as we know it, has long been a cultural imaginary, but has rarely been as topical as it is today. Beyond the phantasmagoria of violence, depression and despair, the conviction of being doomed has always been a challenge to imagine a new, post-apocalyptic world, be it utopian or dystopian. Beyond questions of immediate survival, there is a growing concern about how to educate humanity for a new life after the end of this world. In this volume, the editors, Michael A. Peters and Thomas Meier, renowned scholars of educational and apocalyptic studies, have brought together 31 contributions that offer a diversity of perspectives on such post-apocalyptic education, from abstract philosophical reflections to applied studies, from historical and political analyses of how we got into the current situation of global devastation to decolonial perspectives and essayistic explorations.
Gesehen am 01.10.2025